The Connotative Etymology of Twriyah and its Legal Position - Attaullah; Hayat, Khizar (Journal of Islamic and Religious Studies, 2017)
Twriyah in a speech or word contains multiple meanings having different interpretations of its primary meaning. This article represents the linguistic and connotative concept of Twriyah and T’ryd in the light of Qur’an, hadith, Sirat, the views of various jurists. By analytical study of the available literature it is concluded that there is difference between using Twriyah and Falsification. There are several rules which regulate the use of Twriyah in special circumstances. All Messengers of Allah have never give false statements in any case, however they often used Twriyah in their statements. This article elaborated the various meanings and situations of Twryh in the light of Islamic teachings.